Shareholder litigation rights and capital structure decisions - Nguyen, Nam H.; Phan, Hieu V.; Lee, Eunju (Journal of Corporate Finance, 2020)
We exploit the staggered adoption of the universal demand (UD) laws across U.S. states, which impedes shareholder rights to initiate derivative lawsuits, as a quasi-natural experiment to examine the relation between shareholder litigation rights and firm capital structures. We find that weaker shareholder litigation rights due to the UD laws adoption lead to higher financial leverage, which enhances firm value. Furthermore, the positive relation between the UD laws adoption and financial leverage is more pronounced for firms exposed to higher shareholder litigation risk ex ante or financially constrained firms. Our evidence is consistent with lower shareholder litigation threats motivating firms to increase financial leverage.